Behaviour of GGBS-dolomite geopolymer concrete beam-column joints under monotonic loading. (June 2020) - Saranya, P.; Nagarajan, Praveen; Shashikala, A.P.
Abstract: Geopolymer concrete (GPC) is a cementless concrete in which polymerization gives strength to concrete. In this present study, geopolymer concrete was developed from Ground Granulated Blast furnace Slag (GGBS) and dolomite. The behaviour of GGBS-dolomite geopolymer concrete was found to be brittle in nature. Experimental investigations were conducted to evaluate the effect of the addition of steel fibres to GGBS-Dolomite geopolymer concrete. Improved engineering properties were observed for steel fibre reinforced geopolymer concrete. The performance of beam-column joints was monitored with the addition of 0.25, 0.5 and 0.75% steel fibres by volume of concrete under monotonic loading. Parameters such as ultimate load, energy absorption capacity, ductility index and crack behaviour of steel fibre reinforced geopolymer concrete were compared with geopolymer concrete (without steel fibres). Higher ductile behaviour, energy absorption and toughness were observed along with the addition of steel fibres. The Performance of beam-column joints was evaluated by finite element method and compared with experimental results. Parametric studies were done by numerical methods and concluded that the GGBS-dolomite GPC beam-column joint has an improved load carrying capacity when compared to cement concrete beam-column joints with ductile detailing as per IS-13920 2016.